Entwined evolution how innovation networks foster collaborative growth in East Africa’s edible insect value chain - Ndung’u, N.; Isaboke, H.; Nyarindo, W.; Otieno, M.; Kinyuru, J. (University of Embu, 2025)
The introduction of edible insects as a protein source has gained traction in East Africa, with various multidisciplinary initiatives promoting insect production and consumption. However, there remains a limited understanding of the innovation networks, roles of different actors, and linkages that influence the development of this sector. This study employed social network analysis and exponential random graph models (ERGMs) to examine data from 220 cricket farmers in Masaka, Uganda, and western Kenya, focusing on network structures and participation dynamics. Findings revealed a gap between market awareness and actual sales. The institutional network demonstrated high connectivity, with a density of 0.559 and complete reciprocity. The affiliation network showed eigenvector centrality values were 0.128 for Kenya and 0.112 for Uganda, highlighting the importance of key nodes. Masaka’s farmer network was highly centralized (0.605), in contrast to Kisumu (0.478) and Siaya (0.244). While institutional networks exhibited strong cooperation, the affiliation networks revealed weak linkages, suggesting fragmentation among actors that hinders information flow and coordinated action. This study underscores the increasingly vital role of collaboration between research organizations and the private sector in fostering innovation and demand for cricket farming. Additionally, it contributes to network theory by empirically mapping a multi-actor system within an emerging food innovation context. The findings stress the importance of enhancing stakeholder interactions to facilitate adoption and scaling. Policies should promote best practices in production and processing, while also strengthening institutional support by engaging government agencies, NGOs, and research institutions to provide resources, technical assistance, and market linkages.
Keywords: General; Life Sciences; Food & Health; Animal & Veterinary; Entomology; Biology